Surviving intimate partner violent marriage: experiences of women undergoing psychotherapy at Musasa project, Harare. - Shaba, Pueshpa T. (Midlands State University, 2017)
The study examined the nature of recurring violence against women in Harare. It focused on the lived experiences among female victims. Particular attention was given to the forms of violence experienced, reasons for staying in abusive marriages and the surviving mechanisms adopted by the female victims. Qualitative research method was employed to gather the required data with the use of semi- structured interviews. The study findings confirmed the existence of violence in marriages against women in natural forms such as physical abuse and sexual abuse. Various recommendations were noted and these included the need for safe havens in high density suburbs, increased women empowerment educationally and incorporating them in SMEs which enable them to be financially independent, the need for funding of women’s organizations by both government and NGOs